2017
DOI: 10.1016/j.jhydrol.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Did streamflow or suspended sediment concentration changes reduce sediment load in the middle reaches of the Yellow River?

Abstract: a b s t r a c tThe continuous ecological restoration of the Loess Plateau, which aims to reduce the sediment entering into the Yellow River, is known throughout the world for two strategies: the integrated soil conservation project that began in the 1970s, and the ''Grain for Green" project that began in the 1990s. However, the topic of whether the muddy water in the middle Yellow River run clearer remains debatable, and, in fact, response to the topic is reasonably well documented in regard to hydrological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 39 publications
0
47
0
1
Order By: Relevance
“…Z. L. Gao et al () found that generally LUCC in the past 50 years caused a decreasing trend in annual streamflow and a much greater decreasing trend in annual sediment load that consequently resulted in a weakening streamflow–sediment load relationship in seven catchments, and Rustomji et al () illustrated that the mean annual sediment concentration in seven of 11 catchments exhibited a statistically significant decreasing trend over the past 50 years. Wang et al (2016) and J. Zhang, Zhang, Li, Chen, and Lin () used attribution approaches to account for the reduction of sediment load in terms of streamflow and sediment concentration, and their results showed that the streamflow became cleaner both at the catchment scale and in the Yellow River as a whole. On the basis of their annual and daily hydrological data, the relationship of streamflow and sediment load has changed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Z. L. Gao et al () found that generally LUCC in the past 50 years caused a decreasing trend in annual streamflow and a much greater decreasing trend in annual sediment load that consequently resulted in a weakening streamflow–sediment load relationship in seven catchments, and Rustomji et al () illustrated that the mean annual sediment concentration in seven of 11 catchments exhibited a statistically significant decreasing trend over the past 50 years. Wang et al (2016) and J. Zhang, Zhang, Li, Chen, and Lin () used attribution approaches to account for the reduction of sediment load in terms of streamflow and sediment concentration, and their results showed that the streamflow became cleaner both at the catchment scale and in the Yellow River as a whole. On the basis of their annual and daily hydrological data, the relationship of streamflow and sediment load has changed.…”
Section: Introductionmentioning
confidence: 98%
“…Wang et al (2016) and J. Zhang, Zhang, Li, Chen, and Lin (2017) used attribution approaches to account for the reduction of sediment load in terms of streamflow and sediment concentration, and their results showed that the streamflow became cleaner both at the catchment scale and in the Yellow River as a whole. On the basis of their annual and daily hydrological data, the relationship of streamflow and sediment load has changed.…”
mentioning
confidence: 99%
“…Revegetation proceeded very slowly in the MYRB during the base stage and the restraining stage. Since the 1998 flood event over the Yangtze River basin, China has launched the “Grain for Green” programme in the Loess Plateau, which converted cropland to forest and grassland to mitigate water and soil loss (Zhang, Zhang, Li, Chen, & Lin, ). According to a study based on Landsat TM images (Liu, ), the area covered by forest and grassland in the sediment source regions of the Yellow River (mostly in the MYRB) increased by 11,255 km 2 from 1978 to 2014, with 82% increase in 30% coverage area and 94% increase in 70% coverage area occurring between 1998 and 2014.…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that approximately one-third of the global sediment load to oceans is generated from the large rivers originating from the Tibetan Plateau and its neighboring regions [2]. In recent decades, the sediment regimes of these rivers have attracted increasing attention due to public concerns about climate change and increasing human activities [3][4][5][6][7][8][9][10][11]. Human activities, such as infrastructure development, soil conservation, and sand excavation, have played an important role in sediment load variations [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%